Peran Pendidikan Kewarganegaraan dalam Membentuk Identitas Kebangsaan - Randi, Muhammad Sinar; An-Nur, Rosyida; Tamba, Hilyatun Fhinta BR; Hutagalung, Nazwa Aulia Mahatma; Yahman, Kanesha Muradah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to examine the role of Civic Education (PKn) in shaping national identity through a literature review method. Civic education plays a crucial role in instilling national values, love for the homeland, as well as understanding rights and responsibilities as citizens. The literature review findings indicate that Civic Education can foster a strong national identity through holistic and participatory learning. However, its implementation in the field often faces various challenges that require further attention.